Physics classroom interactions: Teaching strategies and practices - Isaac Buabeng (Journal of Research in Science, Mathematics and Technology Education, 2018)
This study investigated the interactions that occurred as part of the learning from a national survey of high school physics teachers in New Zealand (NZ) in relation to decile ranking. Specifically, the study investigated how often particular teaching strategies and practices such as: teaching approaches, teacher feedback and guidance, and ICT usage, occurred during physics teaching. Data were analyzed using descriptive statistical and inferential statistics – MANOVA. Among other things, the study revealed that learners were not exposed to the teaching methods that potentially give them the chance to observe, engage and/or discover expert strategies in context. There was a lack of use of problem-based or inquiry learning models for learning. However, there was no significant difference between teaching in the various decile rankings. The implications of the findings are discussed.